2023
DOI: 10.1108/jmtm-06-2023-0224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of digital orientation on organizational resilience: a dynamic capabilities perspective

Yanzhe Liu,
Minrui Guo,
Zhongyi Han
et al.

Abstract: PurposeThis study aims to investigate the impact of digital orientation (DO) on organizational resilience (OR) and explore the contingency effects of human resource slack and nature of enterprise ownership.Design/methodology/approachThe model hypotheses were tested using fixed effects regression on panel data collected from Chinese A-share listed manufacturing firms spanning from 2007 to 2020.FindingsDO has a positive effect on OR. Human resource slack positively moderates the relationship between DO and OR. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…With the rise of digital technology and the development of the digital economy, the dynamic capability view has become an essential theoretical perspective for research on enterprise digital transformation and innovation management in the digital context [7]. Several studies have found that digital technology can significantly reshape business processes [29], accelerate knowledge flow and sharing [30], and promote different forms of dynamic capabilities [31].…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rise of digital technology and the development of the digital economy, the dynamic capability view has become an essential theoretical perspective for research on enterprise digital transformation and innovation management in the digital context [7]. Several studies have found that digital technology can significantly reshape business processes [29], accelerate knowledge flow and sharing [30], and promote different forms of dynamic capabilities [31].…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%
“…In addressing the identified gaps, this study adopts the dynamic capability view to explore the influence of digital orientation on NPD performance while also considering the potential impact of knowledge intensity on this relationship. The choice of dynamic capabilities as a theoretical framework is justified by its effectiveness in examining a firm's digital transformation [7], value creation and delivery in digital environments [8], and product development [9]. By leveraging the dynamic capability view, this research aims to provide a comprehensive understanding of how digital orientation contributes to NPD performance through dynamic capabilities such as exploitation, exploration, and ambidexterity capabilities, particularly in the context of knowledge-intensive firms, and to offer valuable insights for both theory and practice in the field of management.…”
Section: Introductionmentioning
confidence: 99%
“…First, a DS enhances internal operational efficiency. Highly digitalized firms not only optimize supply chain management processes like inventory, procurement, and production scheduling through technological means such as big data analysis [47,48], they are also assisted with accurately identifying and satisfying customer needs and market preferences [14,49]. By refining support systems for decision-making and effectively allocating internal resources [50], a DS strengthens the company's ability to sustain itself, reducing its dependence on specific external resources-including those provided by governments-thereby diminishing incentives for and the necessity of rent-seeking.…”
Section: Digitalization Strategy and Corporate Rent-seekingmentioning
confidence: 99%
“…However, because rent-seeking is essentially invisible [12], it is imperative to not only audit and restrain such behaviors through state coercion but also to explore alternative methods, particularly through the management practices of enterprises themselves. With the rise of the digital economy, many enterprises have implemented a digitalization strategy, extensively integrating digital technology into their production and operations [13,14]. Digitalization strategy not only reshapes firms' operational models but also offers new opportunities to strengthen their ethical codes and governance structures [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation